Clinical management of comorbid bipolar disorder and obsessive-compulsive disorder: A case series.: BD-OCD comorbidity: A case series. - Amerio, Andrea; Tonna, Matteo; Odone, Anna (Acta Biomedica Atenei Parmensis, 2018)
Background:Apparent comorbidity between bipolar disorder (BD) and obsessive-compulsive disorder (OCD) is a common condition in psychiatry and it has important nosological and therapeutic implications. Although antidepressantsare the first line treatment for OCD, they can induce mood instability in BD. An optimal treatment approach remains to be defined.Methods:Longitudinal clinical observation of three severe OCD patients who developed a manic episode during treatment with different classes of antidepressants.Results: In our cases, three features support the hypothesis of an underlying bipolarity unmasked by the antidepressant used to treat OCD: positive family history for affective disorders, manic switch induced by antidepressantand improvement of affective and obsessive-compulsivesymptoms with mood stabilizers and atypical antipsychotics.Conclusions:Osler’s view that medicine should be treatment of diseases, not of symptoms, is consistent with the approach of mood stabilization as a first objective in BD-OCD patients, as opposed to immediate treatment with antidepressants. Only persistent OCD patients should be prescribed antidepressants in as low a dose as feasible.